2007
DOI: 10.1073/pnas.0702551104
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of rate-limiting motions in enzyme function

Abstract: The ability to use conformational flexibility is a hallmark of enzyme function. Here we show that protein motions and catalytic activity in a RNase are coupled and display identical solvent isotope effects. Solution NMR relaxation experiments identify a cluster of residues, some distant from the active site, that are integral to this motion. These studies implicate a single residue, histidine-48, as the key modulator in coupling protein motion with enzyme function. Mutation of H48 to alanine results in loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
201
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(230 citation statements)
references
References 43 publications
(53 reference statements)
26
201
0
Order By: Relevance
“…This mechanism is supported by other studies where the unbound protein was found to sample conformations close to the bound form (5)(6)(7)34). However, our analysis shows that for only approximately one-third of the proteins with a large conformational change upon association, do the direction and location of motion along one of the lowest normal modes agree well with the observed conformational change.…”
Section: Discussionsupporting
confidence: 80%
“…This mechanism is supported by other studies where the unbound protein was found to sample conformations close to the bound form (5)(6)(7)34). However, our analysis shows that for only approximately one-third of the proteins with a large conformational change upon association, do the direction and location of motion along one of the lowest normal modes agree well with the observed conformational change.…”
Section: Discussionsupporting
confidence: 80%
“…The suggested role of this azurin flexibility, or lack of rigid protein matrix, is to facilitate electron transfer (30). From this perspective, and from the growing evidence that active-site dynamics are critical for enzyme catalysis (31,32), it is notable that the H43F mutation has only a modest impact on SOD1 activity. One explanation might be that the activity of SOD1 is near diffusion control (7) and not limited by dynamics at the observed timescales.…”
Section: Discussionmentioning
confidence: 99%
“…Histidine 48 is at the top of the hinge, and its protonation state is important for this process. More direct evidence for the role of this residue in the conformational change of the isolated enzyme and in the catalytic reaction has been obtained recently with nuclear magnetic resonance methods (13). When the substrate binds, the hinge closes, squeezing out water and creating a hydrophobic environment.…”
Section: Ribonucleasementioning
confidence: 97%